2022 IEEE Globecom Workshops (GC Wkshps) 2022
DOI: 10.1109/gcwkshps56602.2022.10008768
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Based Joint Channel Prediction and Antenna Selection for Massive MIMO with Partial CSI

Abstract: This paper investigates the massive multi-input multi-output (MIMO) system in practical deployment scenarios, in which, to balance the economic and energy efficiency with the system performance, the number of radio frequency (RF) chains is smaller than the number of antennas. The base station employs antenna selection (AS) to fully harness the spatial multiplexing gain. Conventional AS techniques require full channel state information (CSI), which is time-consuming as the antennas cannot be simultaneously conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Since the number of RF chains is smaller than the number of antennas, only an incomplete CSI can be observed and estimated from each pilot transmission. This indicates that acquiring complete CSI eventually leads to extra pilot transmissions and reducing the effective transmission rate [1], [15], [17], [18]. For instance, acquiring complete CSI could occupy more than half of the frame duration for the downlink of a typical time-division duplexing (TDD) massive MIMO system with 64 antennas, 16 RF chains and 4 singleantenna users [15], [19].…”
Section: A Antenna Selection In Massive Mimomentioning
confidence: 99%
See 2 more Smart Citations
“…Since the number of RF chains is smaller than the number of antennas, only an incomplete CSI can be observed and estimated from each pilot transmission. This indicates that acquiring complete CSI eventually leads to extra pilot transmissions and reducing the effective transmission rate [1], [15], [17], [18]. For instance, acquiring complete CSI could occupy more than half of the frame duration for the downlink of a typical time-division duplexing (TDD) massive MIMO system with 64 antennas, 16 RF chains and 4 singleantenna users [15], [19].…”
Section: A Antenna Selection In Massive Mimomentioning
confidence: 99%
“…2) Antenna Selection with Incomplete CSI: Recently, researchers have focused on developing AS algorithms which can directly operate under incomplete CSI [1], [15], [17]. In [15], the authors formulated the AS problem as a combinatorial multi-armed bandit problem when only incomplete CSI is available, and proposed an online AS algorithm using Thompson sampling.…”
Section: A Antenna Selection In Massive Mimomentioning
confidence: 99%
See 1 more Smart Citation
“…The authors therein showed that the Monte-Carlo tree search algorithm achieves better performance than the greedy selection. For the practical scenarios, the authors of [9] proposed a learning based antenna selection to improve the system efficiency with imperfect channel state information (CSI). Moreover, the authors of [10] overcame the nonconvexity by proposing a joint antenna selection and precoding design, which maximizes the system performance to practical constraints.…”
Section: Introductionmentioning
confidence: 99%